(untitled) (International Journal of Environmental Sciences, 2025)
Pig farming is an important economic sector of agriculturally developed countries in the world, including Vietnam. However, this activity is also causing major impacts on the water quality around concentrated pig farming areas. This study was conducted to assess the impact of contract pig-farms on the aquatic environment in Vietnam. 100 pig farms (including 70 contract pig-farms and 30 non-contract pig-farms as controls) in the suburban area of ​​Hanoi city were selected for the study. We conducted a questionnaire survey, collected samples of waste sources, surface water, and groundwater around the contracted and non-contracted pig-farms areas to compare with environmental standards, and calculated the Comprehensive Pollution Index (CPI). The results show that contracted pig farms are seriously affecting surface water quality. In contrast, the impact of contract pig-farms on groundwater quality is unclear. Compared with non-constract pig-farms, the impact on surface water environment of contract pig-farms is significantly higher. The main reason is the difference in pig farming scale (average number of pigs raised is 3.14 times higher) and the waste treatment system does not meet the requirements. To solve this situation, the conversion of traditional pig-farm models to circular pig-farm models, reducing emissions, needs to be implemented soon in the near future.